Hubungan Frekuensi Pemberian Asi dengan Kejadian Mastitis Ibu Menyusui 0-6 Bulan Di Puskesmas Onolalu - Rotua Lenawati Tindaon; Indah Wati Dakhi; Mutiara Ningsih Rambe; Wirlian Zagoto (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2021)
AbstractThe ifrequency iand iduration iof ibreastfeeding ihave ia irelationship iwith ithe ioccurrence iof imastitis ibecause iin ithe ibreast ithere iare ilymphatic iveins ithat idrain imilk iproduction, iif ithe ifrequency iand iduration iof ibreastfeeding iis ioptimal, ithen ibreast iemptying ican ibe icomplete, ilymphatic ivenous iflow iis ismooth, ithus ipreventing imastitis. iThe ipurpose iof ithis istudy iwas ito idetermine iwhether ithere iwas ia irelationship ibetween ithe ifrequency iof ibreastfeeding iand ithe iincidence iof imastitis iin ibreastfeeding imothers i0-6 imonths iin ithe iOnolalu iPublic iHealth iCenter. iThis iresearch imethod iuses ianalytic iwith icross isectional iapproach. iThe isample iin ithe istudy iwas i32 irespondents iwith itotal isampling itechnique. iData ianalysis iusing ichi-square itest. iThe iresults iof ithe istudy iare ithe imajority iof irespondents iaged i20-30 ias imany ias i14 ipeople i(43.8%), ithe imajority iof irespondents iwith ihigh ischool ieducation ias imany ias i13 ipeople i(40.6%), ithe imajority iof irespondents iworking ias iIRT ias imany ias i11 ipeople i(34.4%), ithe imajority iof irespondents iwith iparity iSecundigravida ias imany ias i14 ipeople i(43.8%), ifrom ithe imajority iof i32 irespondents iwith imastitis iincidence ias imany ias i18 irespondents i(56.2%). iThe imajority iof ithe ioptimal ifrequency iof ibreastfeeding iwere i19 irespondents i(59.4%). iBased ion ithe ichi-square istatistical itest ithat ihas ibeen icarried iout, ithe iP-value i(> i0.05) iis i0.006. iThe iresearch ihypothesis iwhich istates ithat ithere iis ia irelationship ibetween ithe ifrequency iof ibreastfeeding iand ithe iincidence iof imastitis iis iproven ior iacceptable. iThe iconclusion ifrom ithe iresults iof ithis istudy iis ithat ithere iis ia irelationship ibetween ithe ifrequency iof ibreastfeeding iand ithe iincidence iof imastitis. iSuggestions iin ithis istudy iare iexpected ito iincrease icounseling ion imatters irelating ito ithe ifrequency iof ibreastfeeding iand ithe iincidence iof imastitis iin ibreastfeeding imothers.Keywords: breastfeeding, duration of breastfeeding, mastitis, incident mastitis,